Governing Climate Change Polycentricity in Action? - Jordan, Andrew; Huitema, Dave; van Asselt, Harro; Forster, Johanna (Physical Sciences, 2018)
The world's foremost experts provide the first systematic test of the ability of polycentric thinking to explain and enhance societal attempts to govern climate change. It is ideal for researchers, practitioners, and advanced students in public policy, international relations, and environmental science. This title is also available as Open Access.